AI REVOLUTIONIZING AIRPORT OPERATIONS: ENHANCING PASSENGER AND BAGGAGE HANDLING FOR EFFICIENCY AND BETTER CUSTOMER EXPERIENCE - Joffin Jose (EPRA International Journal of Multidisciplinary Research (IJMR), 2024)
In several industries, including aviation, artificial intelligence (AI) is having a revolutionary effect. This article examines how AI is transforming airport passenger and baggage handling. It looks at how AI technology may improve airport operations’ overall customer experience, accuracy, and efficiency. The study approach used to obtain insights is discussed, important findings are presented, and ramifications and future directions in this quickly developing topic are concluded in this article.